Flavonoid compounds of tapak liman plant (Elephantopus scaber) as antihyperuricemia - Neni Sri Gunarti; Himyatul Hidayah (Jurnal Ilmiah Farmasi, 2022)
Abstract   Background: Hyperuricemia is a condition where uric acid levels in the blood increase more than 6 mg/dL. Tapak liman (Elephantopus scaber) contains flavonoid compounds that are reported to inhibit the activity of the xanthine oxidase enzyme that causes hyperuricemia. Several Asteraceae tribes have activity as antihyperuricemia, one of which is the tapak liman plant (E. scaber) because of the compounds contained in the flavonoid group which has a working mechanism as an inhibitor of the xanthine oxidase enzyme.Objective: To determine the types of flavonoid compounds in tapak liman (E. scaber) plants that have antihyperuricemic activity.Method: This research is qualitative research using Literature Review Article (LRA) using Google Scholar, PubMed, ResearchGate, and Science direct databases with keywords related to the research topic, namely "Elephantopus scaber, antihyperuricemia, tapak liman, xanthine oxidase, flavonoids".Results: Compounds from the flavonoid group in tapak liman that have the potential as antihyperuricemia are luteolin compounds, luteolin-7-glucoside, quercetin, and rutin with the mechanism of inhibiting the activity of the xanthine oxidase enzyme.Conclusion: compounds from the flavonoid group in tapak liman that have the potential as antihyperuricemic compounds are luteolin, luteolin-7-glucoside, quercetin, and rutin.Keywords: Elephantopus scaber, antihyperuricemia, tapak liman, xanthine oxidase, flavonoids Intisari  Latar belakang: Hiperurisemia merupakan suatu kondisi terjadinya peningkatan kadar asam urat dalam darah lebih dari 6 mg/dL. Tapak liman (E. scaber) mengandung  senyawa flavonoid yang dilaporkan dapat menghambat aktivitas enzim xantin oksidase penyebab hiperurisemia. Beberapa suku Asteraceae memiliki aktivitas sebagai antihiperurisemia, salah satunya adalah tanaman tapak liman (E. scaber) karena adanya senyawa yang terkandung yaitu golongan flavonoid yang memiliki mekanisme kerja sebagai inhibitor enzim xanthin oksidase.Tujuan: Mengetahui jenis-jenis senyawa flavonoid dalam tanaman tapak liman (E. scaber) yang memiliki aktifitas sebagai antihiperurisemia.Metode: Penelitian ini merupakan penelitian kualitatif menggunakan Literature Review Article (LRA) menggunakan database Google Scholar, PubMed, ResearchGate dan Science direct dengan kata kunci yang berkaitan dengan topik penelitian, yaitu “Elephantopus scaber, antihiperurisemia, tapak liman, xantin oksidase, flavonoid”.Hasil: Senyawa golongan flavonoid pada tapak liman yang berpotensi sebagai antihiperurisemia yaitu senyawa  luteolin, luteolin-7-glukosida, kuersetin, dan rutin dengan mekanisme menghambat aktivitas enzim xantin oksidase.Kesimpulan: Senyawa golongan flavonoid pada tapak liman yang berpotensi sebagai antihiperurisemia yaitu senyawa  luteolin, luteolin-7-glukosida, kuersetin, dan rutinKata kunci : Elephantopus scaber, antihyperuricemia, tapak liman, xanthine oxidase, flavonoid